Supplementation of Lactobacillus plantarum (TCI227) Prevented Potassium-Oxonate-Induced Hyperuricemia in Rats - Chien, Chih-Yu; Chien, Yu-Jou; Lin, Yung-Hao; Lin, Yung-Hsiang; Chan, Shu-Ting; Hu, Wei-Chun; Wu, Han-Fang; Chiang, Chi-Fu; Hsu, Chin-Lin (Nutrients, 2022)
Hyperuricemia (HC) is one of the important risk factors for gout, arteriosclerosis, and cardiovascular disease. Animal studies have shown that Lactobacillus plantarum can improve microbiota and immune regulation, as well as inhibit uric acid production. However, it is not clear whether L. plantarum can improve HC and intestinal microbiota. We used potassium oxonate (PO) to induce HC in male SD rats and then treated them with L. plantarum TCI227 in a dose-dependent manner (HC + LD, HC + MD, HC + HD) for 4 weeks. We examined organ weight, conducted biochemical examinations of blood and urine, and analyzed the intestinal microbiota in feces through a 16s rDNA sequence analysis. In this study, TCI227 improved body weight, decreased creatinine and serum uric acid, and increased urine uric acid compared to the HC group. Furthermore, TCI227 increased short-chain fatty acids (SCFAs). In the fecal microbiota (family), TCI227 increased the level of Lactobacillaceae and then decreased the levels of Deferribacteres and Prevotellaceae compared to the HC group. Finally, in the fecal microbiota (genus), TCI227 decreased the level of Prevotella and then increased the levels of Lactobacillus and Ruminococcus compared to the HC group. This study suggested that TCI227 can improve HC and can change the composition of intestinal microbiota in PO-induced male HC SD rats.